Analysis of environmental benefits associated with the incorporation of Waelz slag into fired bricks using LCA. (20th April 2018) - Muñoz, I.; Cifrian, E.; Andrés, A.; Miguel, G. San; Ruiz, D.; Viguri, J.R.
Graphical abstract: Highlights: Impact on climate change of bricks incorporating Waelz slag is reduced by 11.8%. Waelz slag bricks benefit from impact savings affecting human toxicity category. Higher air emissions during firing offset benefits due to soil emission savings. Overall environmental benefits of Waelz slag incorporation to bricks is marginal. Increased CDW recycling does not improve environmental performance. Abstract: A comparative cradle-to-grave LCA shows that incorporating Waelz slag into ceramic bricks generates lower impact on climate change and reduces the impact on freshwater ecotoxicity and fossil depletion. These benefits are attributable to impact savings due to avoiding the landfilling of the slag and reduced fuel demand during the manufacturing stage. However, due to the higher SO2 and HF emissions generated in the firing of slag containing bricks, these benefits are offset by higher impacts on human toxicity and terrestrial acidification categories. The aggregated results suggest very limited environmental benefits in this practice even taking into account different end-of-life scenarios.